Exotic primitivism of death in classical Hollywood living dead films - Outi Hakola (Ilha do Desterro, 2012)
The classical Hollywood horror exhibited the undead monsters, such as mummies, zombies and vampires, at the time when cultural practices of death and dying were changing in the United States. Consequently, the way death is handled in these films is connected to the ongoing marginalization of death. In the classical films, heroes represent modern, medicalized, scientific and marginalized death. In contrast, the undead represent traditional, or irrational and magical, death. When the heroes hunt down and kill the monsters, they also claim the superiority of modern death. Furthermore, the exclusion of traditional death is highlighted by using (post)colonial tensions. The non-western monsters and realm of the world stand for traditional death and the past whereas western heroes represent modern death and the future. This article concentrates on how the classical living dead films narrate the cultural tension between the waning (traditional) and emerging (modern) practices of death.